Tinjauan Yuridis terhadap Pengalihan Utang (Over Credit) Dibawah Tangan Atas Perjanjian Leasing Kendaraan Mobil - Meidah, Nuryanah Tirostiah; Hidayat, Anwar; Abas, Muhamad (Wajah Hukum, 2023)
On the basis of Pancasila's mandate and the 1945 Constitution, numerous economic activities were carried out during the period of national economic development to achieve a just and prosperous society. Leasing is one type of business activity that can be carried out in the financial and non-financial sectors to help the economy grow. A lease is an agreement between the lessor and the lessee to rent a particular kind of capital goods that the lessee chooses. In point of fact, numerous breakthroughs are regarded as in violation of the leasing party's agreements. Where this is known as over credit (obligation move) under the hands or without the information on the important gatherings, in particular renting. The issue lies in the connection between Law Number 42 of 1999 concerning Fiduciary Guarantees and the implementation of over credit (debt transfer) in car leasing agreements as well as the factors that prevent it. The exploration technique utilizes an observational juridical methodology, as per the creators, as the creators make sense of that the presence of these occasions requires a comprehension for the general population about the lawful component of over credit (move of obligation) in credit, particularly for vehicle vehicles. Based on these issues, scientists need to thoroughly analyze the component of over credit (obligation move) in renting (renting) related with Regulation Number 42 of 1999 concerning Trustee Assurances.